Moscas-das-frutas Diptera: Tephritidae na região nordeste do Pará - Ayres, Alvaro Remigio (Universidade Federal Rural do Semi-Árido, 2015)
Fruit flies (Diptera: Tephritidae) are a group of phytophagous insects with species that can take a pest status in a wide variety of fruit. Brazilian studies have been taken towards a range in biodiversity, population dynamics and interactions with hosts and parasitoids in different regions. However, in Brazilian Amazon, especially in the state of Pará, information about bioecology of these insects are sparse. Therefore this study aimed to do a faunistic analysis and to verify the profile of population fluctuation of tephritids at orchards in the city of Castanhal, Pará, besides to become fruit flies host and parasitoid known in this city and in others cities of that State. For the faunistic analysis and population dynamics it was collected tephritids with the aid of 15 McPhail traps which contained 400 ml of hydrolyzed maize protein as bait, in the period between January and December 2014. The traps were distributed in orchards in five locations in Castanhal, and they were installed on the treetops at a distance of 1.8 meter from the ground. Through faunistic analysis of harvested species it was measured the Shannon diversity index, Simpson dominance, Hill equitability modified, in addition to the recording of frequency, constancy, wealth and abundance of dominant species. For the fly fluctuation population fly/ trap / day (MAD) monthly index was related to the monthly values of rainfall (mm), relative humidity of air (%) and average temperature of air (oC) in such region. The study concerning to host and parasitoid fruit flies was performed by collecting fruits between November 2013 and January 2015 in Castanhal, São Francisco do Pará, Igarapé Açu, Iriuia, Capanema and Santa Luzia Pará, all of them cities in the state of Pará. The fruits were taken, brought to a laboratory and placed in plastic trays on a layer of vermiculite and then they were covered with a thin cloth to obtain pupae flies and adult insects (flies and/or parasitoids). It was collected in traps 6.322 tephritids (70.5% females and 29.5% males) which belong to 13 species, 12 from Anastrepha gender and a sample of Ceratitis capitata. Anastrepha obliqua was the only dominant specie and the most frequent one (89.60%), followed by Anastrepha distincta (5.97%) and Anastrepha leptozona Hendel (1.37%). It was noticed an increasing value of Simpson index (0.81) and intermediate values in indexes of Shannon (0.49) and Hill (0.62). There were tephritids captures in traps in all sampling months, with the highest population peak of Anastrepha registered in January, October, November and December. There was no significant correlation between fruit flies population dynamics and climatic parameters that have been studied. It was sampled twenty-eight fruit species which belong to 16 botanical families. It was obtained eight species of Anastrepha directly from host insects, with A. oblique predominance, and three parasitoid species Braconidae, highlighting Doryctobracon areolatus
Fruit flies (Diptera: Tephritidae) in northeastern Pará
Keywords: Flies the fruit; bioecology; tephritids; Amazon; Prague fruit; Moscas-das-frutas; Bioecologia; Tefritídeos; Amazônia; Praga de frutífera; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA